ANALISIS PENGENDALIAN INTERNAL TERHADAP PEMBAYARAN TOP UP FLAZZ PADA PT. TRANS JAKARTA - Andriyan Andriyan; Ridwan Saleh (STIE Muhammadiyah Jakarta, 2020)
PT. Transjakarta is a transportation company that uses an electronic ticket system. The ticket system at the Transjakarta bus stop since 2013 uses an electronic card (e-ticketing), instead of cash. One of these cards is the Flazz card issued by Bank BCA. However, the cash deposit from the sale of the flazz top up from Transjakarta to Bank Bca still experiences constraints, there is a difference every day. Then the need for internal control in the payment process and reconciliation between Bank Bca billing data and top up cash payments in the Transjakarta. So far the two reports that should have been balanced, in fact never happened. That is why reconciliation is needed and the causes of the differences are sought so that a balanced report can be produced. This study aims to determine the implementation of internal control on the concept of components according to COSO. The author uses descriptive methods with the type of qualitative analysis, by reviewing the application of elements of internal control by describing the facts that exist in the field, and analyzing the application of these elements with reference to COSO. The results show that in general the internal controls applied for top up flazz payments have met and are in accordance with the concepts and principles of internal control according to COSO. However, the implementation of the concept of internal control components needs to be refined to be more effective, namely the environmental control, risk assessment and monitoring components.